Increased Orbitofrontal Brain Activation after Administration of a Selective Adenosine A2A Antagonist in Cocaine Dependent Subjects - Moeller, F. Gerard; Steinberg, Joel L.; Lane, Scott D.; Kjome, Kimberly L.; Ma, Liangsuo; Ferre, Sergi; Schmitz, Joy; Green, Charles E.; Bandak, Stephen I.; Renshaw, Perry F.; Kramer, Larry A.; Narayana, Ponnada A. (Frontiers in Psychiatry, 2012)
Background: Positron Emission Tomography imaging studies provide evidence of reduced dopamine function in cocaine dependent subjects in the striatum, which is correlated with prefrontal cortical glucose metabolism, particularly in the orbitofrontal cortex. However, whether enhancement of dopamine in the striatum in cocaine dependent subjects would be associated with changes in prefrontal cortical brain activation is unknown. One novel class of medications that enhance dopamine function via heteromer formation with dopamine receptors in the striatum is the selective adenosine A2A receptor antagonists. This study sought to determine the effects administration of the selective adenosine A2A receptor antagonist SYN115 on brain function in cocaine dependent subjects. Methodology/Principle Findings: Twelve cocaine dependent subjects underwent two fMRI scans (one after a dose of placebo and one after a dose of 100 mg of SYN115) while performing a working memory task with 3 levels of difficulty (3, 5, and 7 digits). fMRI results showed that for 7-digit working memory activation there was significantly greater activation from SYN115 compared to placebo in portions of left (L) lateral orbitofrontal cortex, L insula, and L superior and middle temporal pole. Conclusion/Significance: These findings are consistent with enhanced dopamine function in the striatum in cocaine dependent subjects via blockade of adenosine A2A receptors producing increased brain activation in the orbitofrontal cortex and other cortical regions. This suggests that at least some of the changes in brain activation in prefrontal cortical regions in cocaine dependent subjects may be related to altered striatal dopamine function, and that enhancement of dopamine function via adenosine A2A receptor blockade could be explored further for amelioration of neurobehavioral deficits associated with chronic cocaine use.